Topical potent corticosteroids and R-CDOP improved mycosis fungoides after 20 years treatment as tinea corporis - Hong Nguyen, Chuyen Thi; Thanh Nguyen, Huan; Huong Tran, Giang; Thi Tuyet Ngo, Hanh; The Van, Trung (Trends in Immunotherapy, 2022)
A 62-year-old woman reported with progressive pruritus rash that persisted on her buttocks and extremities for a duration of twenty years. She was initially diagnosed with tinea corporis but then the morphological and histological features were consistent with MF. As MF is considered as a “great imitator”, it is important to emphasize that cutaneous characteristics, skin biopsy, histology, and immunohistology may need to be performed in patients with chronic dermatoses resistant to treatment to rule out the underlying malignancy.